Age-congruency and contact effects in body expression recognition from point-light displays (PLD) - Pollux,Petra M.J.; Hermens,Frouke; Willmott,Alexander P. (PeerJ, 2016)
Recognition of older people’s body expressions is a crucial social skill. We here investigate how age, not just of the observer, but also of the observed individual, affects this skill. Age may influence the ability to recognize other people’s body expressions by changes in one’s own ability to perform certain action over the life-span (i.e., an own-age bias may occur, with best recognition for one’s own age). Whole body point light displays of children, young adults and older adults (>70 years) expressing six different emotions were presented to observers of the same three age-groups. Across two variations of the paradigm, no evidence for the predicted own-age bias (a cross-over interaction between one’s own age and the observed person’s age) was found. Instead, experience effects were found with children better recognizing older actors’ expressions of ‘active emotions,’ such as anger and happiness with greater exposure in daily life. Together, the findings suggest that age-related changes in one own’s mobility only influences body expression categorization in young children who interact frequently with older adults.
Keywords: Body expression recognition; Age congruency; Contact effect